Occurrence of methicillin-resistant Staphylococcus aureus in pets and their owners in rural and urban communities in Trinidad - Naomi Scott; Christopher Seeraj; Brandon Satram; Natalie Michelle Sandy; Keenan Seuradge; Brittany Seerattan; Ishta Seeram; Alva Stewart-Johnson; Abiodun Adesiyun (Journal of Infection in Developing Countries)
Introduction: The occurrence of methicillin-resistant Staphylococcus aureus (MRSA) in pets and their owners has increased due to the misuse and abuse of antibiotics. This study compared the prevalence of MRSA and Staphylococcus aureus strains in pets and their owners in urban and rural communities in Trinidad.